PENGARUH PENGAWET BEKU (CRYOPRESERVATION) TERHADAP KADAR EPIDERMAL GROWTH FACTOR (EGF) PADA SELAPUT AMNION - Ety Retno S; Gunawan Effendi; Gatut Suhendro; I. Handojo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
to measure the difference of EgF concentration in between fresh amniotic membranes and with cryopreservation in 16 amnioticmembranes. Each amniotic membrane was divided into two parts. the first part was extracted in fresh forms and the second partunderwent cryopreservation with glycerol 50% and was stored at –80° C during 1 month before extraction. Both parts of the membranewere extracted using ultrasonic disintegrator and concentration of EgF was measured from the obtained extract using ELISA method.the average concentration of EgF in the fresh amniotic membrane was 122.76 ± 11.59 pg/g while the average concentration of EgFin the amniotic membrane underwent cryopreservation was 99.34 ± 9.49 pg/g. Average degradation of EgF concentration due tocryopreservation is 18.49% ± 10.20%. EgF concentration in fresh amniotic membrane is significantly higher than the EgF concentrationin amniotic membrane underwent cryopreservation (p = 0.000). Degradation of EgF concentration due to cryopreservation at 95%fidence interval is 12.33% to 24.66%